GAMIFICATION SEBAGAI STRATEGI PENINGKATAN KUALITAS BELAJAR MAHASISWA JURUSAN TEKNIK INFORMATIKA DAN KOMPUTER UNIVERSITAS NEGERI MAKASSAR - Nur Fakhrunnisaa; Rafika Hutami Putri; Marwan Ramdhany Edy; Armiana Armiana; Zainab Zainab; Muh Juharman (Sakura Digital Nusantara, 2023)
Gamification is a step that can be taken in helping students achieve their learning goals. In general, students do not like to do repetitive work for a long time, but are willing to spend a lot of time playing games. This study aims to see students' perceptions of the application of Gamification in learning in the Department of Informatics and Computer Engineering, Makassar State University. This descriptive research was conducted to see student responses after application. Students of Makassar State University in the Department of Informatics and Computer Engineering consisting of 2 study programs, namely Computer Engineering and Informatics and Computer Engineering Education. The data collection technique uses a Google Form questionnaire with 25 statements. Statements are grouped into two parts, namely favorable and Unfavorable statements, which are statements that support and do not support an object. Data obtained through the Likert Scale using qualitative descriptive statistics. This analysis is intended to describe the characteristics of the data on each variable. The results showed that the application of Gamification in active learning can improve learning performance in student learning